2009
DOI: 10.1007/s10048-009-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

A Copine family member, Cpne8, is a candidate quantitative trait gene for prion disease incubation time in mouse

Abstract: Prion disease incubation time in mice is determined by many factors including genetic background. The prion gene itself plays a major role in incubation time; however, other genes are also known to be important. Whilst quantitative trait loci (QTL) studies have identified multiple loci across the genome, these regions are often large, and with the exception of Hectd2 on Mmu19, no quantitative trait genes or nucleotides for prion disease incubation time have been demonstrated. In this study, we use the Northpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Modelling cannot estimate the number of sub-clinically infected carriers, and the discrepancy between numbers of clinical cases and prevalence estimates from 512 JDF Wadsworth et al population screening remains unexplained [16][17][18][19]. Incubation periods in human prion infections, even in the absence of a species barrier, may exceed five decades [6,20,21], and multiple genetic loci in addition to the PrP gene are known to influence prion incubation periods in mice [22][23][24][25] and susceptibility in humans [26,27]. Asymptomatically infected carriers appear to have transmitted vCJD prion infection and disease to others via blood transfusion [28][29][30] or blood products [31].…”
Section: Introductionmentioning
confidence: 99%
“…Modelling cannot estimate the number of sub-clinically infected carriers, and the discrepancy between numbers of clinical cases and prevalence estimates from 512 JDF Wadsworth et al population screening remains unexplained [16][17][18][19]. Incubation periods in human prion infections, even in the absence of a species barrier, may exceed five decades [6,20,21], and multiple genetic loci in addition to the PrP gene are known to influence prion incubation periods in mice [22][23][24][25] and susceptibility in humans [26,27]. Asymptomatically infected carriers appear to have transmitted vCJD prion infection and disease to others via blood transfusion [28][29][30] or blood products [31].…”
Section: Introductionmentioning
confidence: 99%
“…These included PRNP, RARB-THRB, STMN2, HECTD2, SPRN, ZBTB38-RASA, BACE, MTMR7, NPAS2, PLCD, CPNE8, SOD1, STCH and CTSD [2,3,19,21,22,29,30,36]. No CNV overlapping these genes was found in more than one individual in a case or control group (table 1 supplementary).…”
Section: Cnvs Overlapping Loci Of Potential Relevance To Prion Diseasementioning
confidence: 85%
“…Several large-scale association studies have reported a role for large CNVs in susceptibility to several human conditions including idiopathic epilepsy, attention deficit hyperactivity disorder, schizophrenia, bipolar disorder, mental retardation, autism, and Alzheimer's disease [1,6,13,14,25,26,40] [2,3,19,21,22,29,30,36]. As a generalisation, few common structural genetic variations are risk factors in common diseases [10], whereas several rare CNVs, including whole or partial gene deletions and/or duplications are known to be major risk factors and/or dominantly inherited disease causing mutations in neurodegenerative diseases [1,13,14,25,26,35,40].…”
Section: Introductionmentioning
confidence: 99%
“…PCR and sequencing reactions were carried out as previously described [17] and run either on a MegaBACE1000 (Amersham Biosciences) or 3730 capillary sequencer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%